Vancouver 1983: Indrukwekkend, maar twyfelagtig - Wyk, D. J. C. van (Hervormde teologiese studies, 1986)
Vancouver 1983: Impressive, but dubious This article is a short summary of the constitution, course and content of the 6th General Assembly of the World Council of Churches which took place during 1983 in Vancouver, Canada. It is a short summary of the most important presentations, reports and declarations. The article is concluded with some critical remarks on the World Council of Churches in general and in particular on the Vancouver meeting.